The Relevance of Size Matching in Self‐assembly: Impact on Regio‐ and Chemoselective Cocrystallizations. Issue 51 (11th August 2020) - Lin, Jing‐Xiang; Daolio, Andrea; Scilabra, Patrick; Terraneo, Giancarlo; Li, Hongfan; Resnati, Giuseppe; Cao, Rong
Abstract: Decamethonium diiodide is reported to perform the chemo‐ and regioselective encapsulation of para ‐dihalobenzenes through the competitive formation of halogen‐bonded cocrystals starting from solutions that also contain ortho and meta isomers. Selective caging in the solid occurs even when an excess ortho or meta isomers, or even a mixture of them, is present in the solution. A prime matching between the size and shape of the dication and the formed dianions plays a key role in enabling the selective self‐assembly, as proven by successful encapsulation of halogen‐bond donors as weak as 1, 4‐dichlorobenzene and by the results of cocrystallization trials involving mismatching tectons. Encapsulated para ‐dihalobenzenes guest molecules can be removed quantitatively by heating the cocrystals under reduced pressure and be recovered as pure materials. The residual decamethonium diiodide can be recycled with no reduction in selectivity. Abstract : Making resolutions : Decamethonium diiodide demonstrates regio‐ and chemoselective cocrystallization with para ‐dihalobenzenes over its isomers thanks to the size‐/shape‐matching effect and hierarchical halogen bonds, which make it a promising reagent for resolving dihalobenzene mixtures.